Pengaruh pendidikan kesehatan dengan media audiovisual dan media booklet terhadap perilaku caregiver dalam mencegah tuberkulosis pada anggota keluarga - Sri Nur Hartiningsih (Health Sciences and Pharmacy Journal, 2018)
Recently, tuberculosis is still a global health problem in the world as well as in Indonesia. Millions of people die and contract tuberculosis every year. Various strategies and efforts are made to reduce the incidence of TB one with health education. Health education for more effective results required an educational media. Audiovisual media and booklets are considered interesting media. This study aims to know the effect of health education with audiovisual and booklet media toward caregiver behavior in preventing tuberculosis in family members. The research used Quasy experiment approach and one group pretest-posttest with control group design. This study was conducted in 2 health centers in Bantul district, with a total sample of 30 respondents The results of this study indicated that in the intervention group there was an increase in TB prevention behavior score of 28.46. This number is more than in the control group which is equal to 9. The comparison test results are obtained p = 0.000. The conclusion of this study was that health education with audiovisual media can improve caregiver behavior in preventing tuberculosis in family members.